2020
DOI: 10.3389/fimmu.2020.00095
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB Duplications in the Promoter-Variant HIV-1C LTR Impact Inflammation Without Altering Viral Replication in the Context of Simian Human Immunodeficiency Viruses and Opioid-Exposure

Abstract: Recent spread of the promoter variant (4-κB) Human immunodeficiency virus-1 clade C (HIV-1C) strain is attributed to duplication of the Nuclear Factor Kappa B (NF-κB) binding sites and potential increased heroin consumption in India. To study the underlying biology of 4-κB HIV-1C in rhesus macaques, we engineered a promoter-chimera variant (4NF-κB) Simian Human Immunodeficiency Virus (SHIV) by substituting the HIV-1C Long Terminal Repeat (LTR) region consisting of 4 NF-κB and 3 Sp-1 sites with the correspondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Similarly, we observed that the length of this part of clade C LTRs is also increasing, and that an increasing length is frequently associated with additional putative NF-κB sites. Notably, it has been reported that HIV-1 clade C strains containing an additional NF-κB, NF-κB-like, or RBEIII site in the viral promoter are replacing the prototype subtype C viruses containing three NF-κB sites in India ( Bachu et al, 2012 ; Dave et al, 2020 ). Notably, RBEIII sites for RBF-2 binding are commonly found in the MFNLP region of clade B LTRs ( Estable et al, 1998 ), and the frequency of LTR sequences containing additional RBEIII sites increased independently of their country of origin (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we observed that the length of this part of clade C LTRs is also increasing, and that an increasing length is frequently associated with additional putative NF-κB sites. Notably, it has been reported that HIV-1 clade C strains containing an additional NF-κB, NF-κB-like, or RBEIII site in the viral promoter are replacing the prototype subtype C viruses containing three NF-κB sites in India ( Bachu et al, 2012 ; Dave et al, 2020 ). Notably, RBEIII sites for RBF-2 binding are commonly found in the MFNLP region of clade B LTRs ( Estable et al, 1998 ), and the frequency of LTR sequences containing additional RBEIII sites increased independently of their country of origin (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Many other viruses (PRSSV (see Glossary) (Wang et al 2013 ), RSV (see Glossary) (Masaki et al 2011 ), HIV-1C (see Glossary) (Dave et al 2020 ; Hiscott et al 2001 ), HBV (see Glossary) (Hiscott et al 2001 ; Liu et al 2020 ), HCV (Hiscott et al 2001 ), HIV (Pahl 1999 ), EBV (see Glossary) (Hiscott et al 2001 )) have been proven to use the described NF-κB pathway for replication. This offers a wide area of therapeutic applications for vagal nerve stimulation.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Opioids have been shown to upregulate the expression of CCR5 while downregulating the expression of its cognate β-chemokine production by acting through µ-opioid receptor in macrophages and microglia, thereby boosting the entry of R5 tropic viruses in these target cells (21)(22)(23)(24). Opioids and HIV synergistically act to activate glia and upregulate the expression of cytokines and chemokines, leading, in turn, to neuronal damage and development of hyperalgesia (25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%